Progesterone produces antinociceptive and neuroprotective effects in rats with microinjected lysophosphatidic acid in the trigeminal nerve root - Kim Min; Shin Hea; Won Kyoung; Yang Kui; Ju Jin; Park Yoon; Park Jae; Bae Yong; Ahn Dong (SAGE Publishing, 2012)
Abstract Background In our present study, we studied the role of demyelination of the trigeminal nerve root in the development of prolonged nociceptive behavior in the trigeminal territory. Results Under anesthesia, the Sprague-Dawley rats were mounted onto a stereotaxic frame and 3 μL of lysophosphatidic acid (LPA, 1 nmol) was injected into the trigeminal nerve root to produce demyelination. This treatment decreased the air-puff thresholds, persisted until postoperative day 130, and then returned to the preoperative levels 160 days after LPA injection. The LPA-treated rats also showed a significant hyper-responsiveness to pin-prick stimulation. We further investigated the antinociceptive and neuroprotective effects of progesterone in rats undergoing demyelination of the trigeminal nerve root. Progesterone (8, 16 mg/kg/day) was administered subcutaneously, beginning on the operative day, for five consecutive days in the LPA-treated rats. Treatment with progesterone produced significant early anti-allodynic effects and delayed prolonged anti-allodynic effects. The expression of protein zero (P0) and peripheral myelin protein 22 (PMP22) were significantly down-regulated in the trigeminal nerve root on postoperative day 5 following LPA injection. This down-regulation of the P0 and PMP22 levels was blocked by progesterone treatment. Conclusions These results suggest that progesterone produces antinociceptive effects through neuroprotective action in animals with LPA-induced trigeminal neuropathic pain. Moreover, progesterone has potential utility as a novel therapy for trigeminal neuropathic pain relief at an appropriate managed dose and is therefore a possible future treatment strategy for improving the recovery from injury.